Rilievo ed elaborazione di dati laser acquisiti con sistemi MMS in un parco urbano - Dardanelli, Gino; Carella, Marco (GEOmedia, 2013)
This article summarizes the experience gained between 2012 and 2013 by the department of "Civil, Environmental, Aerospace and Materials" of the 'University of Palermo on the integrated survey of Park N. Cass ara in Palermo and the subs equent testing of methods, tools and techniques based on current research regarding the acquisition and process ing of GN SS data and laser-scanner. The work has been address ed in order to select the less expensive and fast techniques to be applied in the acquisition phase. After first monumenting sixteen control points distributed within the site and surveyed by GN SS, then was planned and carried out the survey in NRTK mode of the paths and of the key elements of the park. It was therefore decided to experiment with MM S acquisition of the park through which it was poss ible to acquire data about the morphology of the terrain, the conditions of the state of footpaths, buildings that laid ahead and distribution of street furniture. The point clouds obtained through this technology have been subjected to both automatic and manual procedures to verify that, finally, their actual descriptive poss ibilities of real forms.